Pre-service teachers' learning about inclusive education from an online module - Melanie Martin; Carol Bertram (AOSIS, 2024)
Background: Thousands of South African pre-service teachers have completed an online course to prepare them for school-based practice, which included a unit on inclusive education. Aim: In this article, we present students' responses to a written task to answer the question of what pre-service teachers learned about inclusive education from an online module, called Teacher Choices in Action. Setting: The online module was designed to prepare pre-service teachers for school-based learning through guided analysis of recorded lessons. Methods: Data were analysed from 176 B.Ed. and PGCE (Postgraduate Certificate in Education) students who completed the task in the inclusive education unit of the module. Results: The findings show that half of the coded responses reflected the instructional strategies such as scaffolding and participation, but with minimal emphasis on multilingualism, making connections, breaking down concepts and differentiated pacing, which were emphasised in the module. A quarter of the coded responses focussed on creating a supportive classroom ethos and the remaining quarter reflected teacher disposition (taking responsibility for inclusive teaching and being aware of the barriers to learning and diversity). Conclusion: We conclude by arguing that while we initially approached the data by thinking about who the teacher is as separate from what the teacher does, it became clearer how these are embedded. Contribution: We argue it is helpful to revisit Bernstein's concepts of the instructional discourse (strategies for inclusive pedagogies) being embedded in the regulative discourse (the moral values expected in the classroom of both teachers and learners).